Music as a Means of Improving Concentration - Dražič, Tinkara (Širjenje obzorij o poučevanju glasbe, 2025)
This chapter highlights how music can contribute to improved concentration and, consequently, enhance students' learning achievement. Listening to music during lessons helps create a stimulating learning environment, reduces external distractions, develops cognitive skills, and fosters positive attitudes toward learning. The impact of music on students' learning performance depends on the type of task, the complexity of the music, and the personal characteristics of the listeners. Music with a calm tempo has a soothing effect, enhances concentration, and promotes appropriate behaviour. Classical and jazz music, in particular, have a positive effect on concentration, while faster rhythms can be distracting. Through thoughtful music choices or the inclusion of musical breaks, teachers can increase pupils' concentration and make their learning experience more relaxed and productive. This approach can positively influence learning outcomes and improve the overall classroom climate.